ESTIMASI KOMPONEN RAGAM DAN HERITABILITAS BOBOT BADAN PERIODE STARTER AYAM LOKAL - Ahmad Bayu Saputra; Bercomien J. Papilaya; Rajab Rajab (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2021)
This study aims to determine the diversity and heritability components of the nature of body weight production of local chickens aged 0-4 weeks. The material used in this study were 95 local chickens from 4 male and 20 female. Heritability calculation (h2) uses the nested design method. The results showed the value of heritability (h2) DOC weights in male body weights were 0.429851 and 0.569476 in the third week, while the largest variance component in the third week was 12.28387 and for female in the fourth week was 59.333934 . Heritability (h2) DOC weights for male body weight gain were 0.6840 and 0.5257 in the third week, the variance component given from the largest male was in the fourth week ie 0.39037 and for female in the second week was 0.68931.